STEM teaching competency framework for pre-service teacher: a study in Vietnam - Phuong, Phan Nguyen Truc; Hong, Bui Van; Van De, Dinh (International Journal of Evaluation and Research in Education (IJERE), 2025)
Science, technology, engineering, and mathematics (STEM) education has been emphasized in Vietnam’s new general education curriculum; however, the teaching competencies of pre-service teachers in this area remain underexplored. This study addresses that gap by proposing and validating a STEM teaching competency framework tailored for pre-service teachers. A mixed-methods approach was employed, including literature review, expert interviews, and surveys. The sample consisted of 400 participants— pre-service teachers, in-service teachers, and lecturers—selected through stratified random sampling. Data were collected using questionnaires and analyzed with SPSS 24. Reliability was confirmed using Cronbach’s alpha (0.724) and construct validity was assessed through exploratory factor analysis (EFA). Results indicate that pre-service teachers face challenges in interdisciplinary integration, classroom organization, and technology application. The proposed framework includes five key domains: understanding STEM education, designing integrated lessons, organizing learning environments, implementing instruction, and evaluating and improving teaching practices. This study offers a reliable and practical tool to assess and enhance STEM teaching competencies. Its novelty lies in contextualizing competencies for pre-service teachers in Vietnam. The framework has practical implications for teacher training programs and policy development, and further application across teacher education institutions is recommended.